A Type IIb, but Not Type IIa, GnRH Receptor Mediates GnRH-Induced Release of Growth Hormone in the Ricefield Eel - Chen, Dong; Yang, Wei; Han, Shiying; Yang, Huiyi; Cen, Xin; Liu, Jiang; Zhang, Lihong; Zhang, Weimin (Frontiers in Endocrinology, 2018)
Multiple gonadotropin-releasing hormone receptors (GnRHRs) are present in vertebrates, but their differential physiological relevances remain to be clarified. In the present study, we identified three GnRH ligands GnRH1 (pjGnRH), GnRH2 (cGnRH-II), and GnRH3 (sGnRH) from the brain, and two GnRH receptors GnRHR1 (GnRHR IIa) and GnRHR2 (GnRHR IIb) from the pituitary of the ricefield eel Monopterus albus. Immunoreactive GnRH1 and GnRH3 but not GnRH2 were detected in the pre-optic area, hypothalamus, and pituitary, suggesting that GnRH1 and GnRH3 may exert hypophysiotropic roles in ricefield eels. gnrhr1 mRNA was mainly detected in the pituitary, whereas gnrhr2 mRNA broadly in tissues of both females and males. In the pituitary, immunoreactive GnRHR1 and GnRHR2 were differentially distributed, with GnRHR1 mainly in peripheral areas of the adenohypophysis whereas GnRHR2 in the multicellular layers of adenohypophysis adjacent to the neurohypophysis. Dual-label fluorescent immunostaining showed that GnRHR2 but not GnRHR1 was localized to somatotropes, and all somatotropes are GnRHR2-positive cells and vise versa at all stages examined. GnRH1 and GnRH3 were shown to stimulate growth hormone (Gh) release from primary culture of pituitary cells, and to decrease Gh contents in the pituitary of ricefield eels 12 h post injection. GnRH1 and GnRH3 stimulated Gh release probably via PLC/IP3/PKC and Ca2+ pathways. These results, as a whole, suggested that GnRHs may bind to GnRHR2 but not GnRHR1 to trigger Gh release in ricefield eels, and provided novel information on differential roles of multiple GnRH receptors in vertebrates.